The Pattern of Conflict Handling of Arus Pelangi Non-Governmental Organizations with the Islamic Defenders Front and Hizbut Tahrir Indonesia - Nur Sakinah (The International Journal of Politics and Sociology Research, 2021)
Arus Pelangi is a non-governmental organization (NGO) that specializes in defending the rights of LGBT people in Jakarta. Meanwhile, the Islamic Defenders Front (FPI) and Hizbut Tahrir Indonesia (HTI) are two religious community organizations that always actively refuse if there is something that is considered outside the provisions of religious and community norms. In Indonesia, there are still many people who are homophobic (have a fear of or reject homosexuals) and do not have sufficient information about LGBT, this is because there has not been much discussion about LGBT in the form of scientific discussions, therefore the author wants to know more about homosexuality that is in the end make people become homophobic and put pressure on homosexuals. With this research, it is hoped that it will be able to educate people who experience homophobia or have a fear of homosexuals. The results obtained from this study are social courts. The causes or background why people put pressure on LGBT or homosexual perpetrators can generally be divided into three major parts, namely religious and belief backgrounds, historical backgrounds, and environmental social behavior backgrounds.